2019
DOI: 10.1093/zoolinnean/zlz053
|View full text |Cite
|
Sign up to set email alerts
|

A global analysis of cladoceran body size and its variation linking to habitat, distribution and taxonomy

Abstract: Body size is a functional trait that influences the overall biology and ecology of an organism. Studying the shape of size–frequency distributions and size variability within different scales, approximates the influence of large-scale ecological and evolutionary processes on a species. In this study we examine the patterns of distribution and variability of body size among freshwater Cladocera across different taxonomic levels, geographic distribution and habitat association. Using extensive literature data, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…For all species except salmonids, we considered a trophic class (i.e., predatory invertebrate, primary consumers, primary producers) and a niche trait (average body length of each taxa expressed in μm) obtained from literature sources (Armitage et al, 1995;Balik et al, 2004;Basińska et al, 2014;Benke et al, 1999;Erman & Helm, 1970;Rimet & Druart, 2018;Rizo et al, 2019;Tachet et al, 2010;Vergon & Bourgeois, 1993). For salmonids, individual body lengths obtained from the samplings were allocated into different size classes (Figure S2) for food-web reconstructions.…”
Section: Taxonomic Inventoriesmentioning
confidence: 99%
“…For all species except salmonids, we considered a trophic class (i.e., predatory invertebrate, primary consumers, primary producers) and a niche trait (average body length of each taxa expressed in μm) obtained from literature sources (Armitage et al, 1995;Balik et al, 2004;Basińska et al, 2014;Benke et al, 1999;Erman & Helm, 1970;Rimet & Druart, 2018;Rizo et al, 2019;Tachet et al, 2010;Vergon & Bourgeois, 1993). For salmonids, individual body lengths obtained from the samplings were allocated into different size classes (Figure S2) for food-web reconstructions.…”
Section: Taxonomic Inventoriesmentioning
confidence: 99%
“…Rizo et al [42] investigated patterns of distribution and variability of body size among freshwater Cladocera taxa across different taxonomic levels, geographic distributions and habitat associations. They found that cladoceran body size is a phylogenetically conserved trait, but the observed variation and the varying means between biogeographical regions also suggests the effect of climate on size variability in cladocerans.…”
Section: Introductionmentioning
confidence: 99%